Study the Impacts of a Dry Port Which Suggested in Hassia Industrial City on the Logistic Transportation Sector - Rustum, Akram; Hassan, Bassam; Kheirbek, Yara (Latakia University Journal -Engineering Sciences Series, 2015)
The appearance of revolutionary containerization utilized by maritime transport sector has led to congested seaports. A transfer of a portion of the activities performed inside was suggested. A complement to the sea port became desired, which created the idea of a dryport. We studied the effect of the dryport’s site, planned to be constructed in Hassia industrial city, on the Syrian transport network. We used geographic information systems (GIS) to get the results due potential assistance. Study shows that a dryport increases the efficiency of the transport system, thus reducing the cost and time of transport. Furthermore, Hassia industrial city is especially qualified to establish a dryport, and the eastern region would be the optimal region for such an establishment.